Re-forming the monstrous - Jacobs, Gabriele (Michaelis School of Fine Art, 2023)
Re-forming the Monstrous consists of an installation of ceramic and wooden sculpture accompanied by an audio piece, and an explicatory document. This artistic project aims to critique the entwined social and ecological violence associated with the current era, as governed by hegemonic patriarchal capitalism, with particular reference to Anna Lowenhaupt Tsing and Donna Haraway. In the artwork, this is articulated through an imaginative reinterpretation of selected characters from Greco-Roman mythology. The trope of the Hero who must slay a monster to gain redemption for his transgressions (as in the case of Heracles) is examined and subverted. The process culminates in a sculptural installation in two parts: the first a metaphorical contemplation of the ongoing ecological and social devastation; the second composed of a number of discrete tableaux symbolising a sanctuary for the monster. In this figuration, the monster, represented by particular South African and domestic fauna, provides the departure point to consider issues of the environment, queerness and care through the immersive format of installation. The writing of queer theorists, José Estaban Munoz' s and Jack Halberstam is considered with reference to this body of work, as well as artworks by a number of local and international artists, in the context of imagining a creative salve to current global crises.